ANALYSIS OF CHANGES IN THE ACTIVITIES OF RURAL MEDICAL CENTERS IN THE FERGANA VALLEY (Scientific journal of the Fergana State University, 2026)
This article analyzes the activities of rural medical stations in the Fergana Valley and their changes on a scientific basis. The article also presents the number of rural medical stations in the Republic and the Fergana Valley in the early years of independence and their growth with specific figures. The article analyzes the material and technical condition of rural medical stations in the early years and their improvement in recent years.